Konservasi Tanah Pada Perkebunan Kelapa Sawit Tanaman Menghasilkan Di Pt. Citra Putra Kebun Asri Jorong Tanah Laut - Herry Iswahyudi (Program Studi Budidaya Tanaman Perkebunan, Politeknik Hasnur, 2020)
Observations of soil conservation are carried out using qualitative method with descriptive, wwhere field activities include observations of vegetatif method, mechanic method and chemical method. Oil Palm plantation of PT. Citra Putra Kebun Asri uses 2 soil conservation methods, that is vegetative and mechanical methods. Vegetative method is carried out by utilizing litter (mulching), namely by arranging the oil palm fronds of prunning result in dead gawns with the aim of supressing growth of weeds and prevent erosion. Mechanical method is done by applying trenches and rorak. Trenches just made in low areas with the aim of being a drainage channel for block are not inundated and making rorak as a shelter for crop residues in the dry season to keep it moist.